On becoming fearless in love, work, and life - Huffington, Arianna Stassinopoulos (New York Little, Brown, 2006)
What are you afraid of? Being assertive? Looking fat? Getting older? Going broke? Whatever your fear, women everywhere confront the same fears every day. Huffington believes that conquering fear is crucial to living a full life and to making a difference in the world, and in this manifesto, she inspires us to take on the task. Huffington is fearless, but not by nature; she's had to learn to overcome her fears and relies on these hard-won lessons every day. She shows how to be bold from the inside out--from feeling comfortable in our own skin to getting what we want in love and at work to changing the world. In order to live a happy, fulfilling life, we need to reach the point where our fears do not stop us from daring to think new thoughts, take risks, fail, start again, and, ultimately, succeed.
Keywords: Women--Psychology.